2013
DOI: 10.1104/pp.113.224972
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Vacuolar Sugar CarrierAtSWEET16Modifies Germination, Growth, and Stress Tolerance in Arabidopsis  

Abstract: Here, we report that SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTER (SWEET16) from Arabidopsis (Arabidopsis thaliana) is a vacuole-located carrier, transporting glucose (Glc), fructose (Fru), and sucrose (Suc) after heterologous expression in Xenopus laevis oocytes. The SWEET16 gene, similar to the homologs gene SWEET17, is mainly expressed in vascular parenchyma cells. Application of Glc, Fru, or Suc, as well as cold, osmotic stress, or low nitrogen, provoke the down-regulation of SWEET16 messenger RNA accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
233
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(260 citation statements)
references
References 65 publications
9
233
0
Order By: Relevance
“…This may related to the fact that the sugars are effective in the regulation of osmotic pressure in plant cells. Researchers have also shown that over-expression of vacuole sugar transporter AtSWEET16 may modify the process of stress tolerance in Arabidopsis (Klemens et al 2013). Sugar-induced tolerance to the herbicide atrazine in Arabidopsis seedlings has also been shown to be related to the oxidative and xenobiotic stress responses (Sulmon et al 2006).…”
Section: Expressions Of Sugar Metabolism Related Genesmentioning
confidence: 99%
“…This may related to the fact that the sugars are effective in the regulation of osmotic pressure in plant cells. Researchers have also shown that over-expression of vacuole sugar transporter AtSWEET16 may modify the process of stress tolerance in Arabidopsis (Klemens et al 2013). Sugar-induced tolerance to the herbicide atrazine in Arabidopsis seedlings has also been shown to be related to the oxidative and xenobiotic stress responses (Sulmon et al 2006).…”
Section: Expressions Of Sugar Metabolism Related Genesmentioning
confidence: 99%
“…Many SWEET genes in different plants are the key factors that regulate the redistribution of soluble sugar and respond to many abiotic stresses at the transcriptional level, indicating that they may be closely related to plant stress response (Yuan and Wang 2013;Klemens et al 2013;Seo et al 2011). The mutants have defects of AtSWEET11 and AtSWEET12 affects freezing tolerance in Arabidopsis (Hir et al 2015).…”
Section: Expression and Putative Functions Of Sweetsmentioning
confidence: 99%
“…AtSWEET15 can be induced by cold, salt and drought stress (Seo et al 2011). Overexpressing AtSWEET16 improved the tolerance to cold stress, osmotic stress and nitrogen availability in Arabidopsis (Klemens et al 2013). In addition, SWEETs from other plants (e.g., Hordeum vulgare, tomato, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of SWEET8/Ruptured pollen grain1 in Arabidopsis, and RNA inhibition of OsSWEET11 (also called Os8N3 or Xa13) in rice, and petunia (Petunia hybrida) NEC1 resulted in male sterility (Ge et al, 2001;Yang et al, 2006;Guan et al, 2008), possibly caused by inhibiting the Glc supply to developing pollen (Guan et al, 2008). Interestingly, two members, SWEET16 and SWEET17, of the family localize to the tonoplast Klemens et al, 2013). Allelic variation or mutations that affect SWEET17 expression caused Fru accumulation in Arabidopsis leaves, indicating that it plays a key role in exporting Fru from leaf vacuoles .…”
mentioning
confidence: 99%